Pengaruh Return on Equity Dan Price To Book Value Terhadap Harga Saham: Studi Kasus Pada Perusahaan Sektor Consumer Goods yang Terdaftar di Indeks SRI-KEHATI - Yulia, Iis Anisa; Widjaja, Ichwan Rahmanu; Putra, Mulyana Gustira (Institut Bisnis dan Informatika Kesatuan, 2023)
The SRI-KEHATI index is one type of index on the Indonesia Stock Exchange. Companies selected and listed on the SRI-KEHATI Index are companies that have concern for the environment and surrounding communities, good corporate governance, participate in the shift to a sustainable economy, and contribute to achieving sustainable development goals both nationally and internationally. The SRI-KEHATI index is an indicator of stock price movements that can be used as a guide for investors who will invest their funds in stocks that have environmental concerns and contribute to a sustainable economy. Based on the SRI-KEHATI index, the stock prices of companies in the consumer goods sector experienced a significant decline for five years from 2017-2021. This decrease can be influenced by several factors such as Return On Equity (ROE) and Price to Book Value (PBV) factors. This study uses fundamental analysis with financial ratio analysis. This study aims to examine the effect of Return On Equity (ROE) and Price to Book Value (PBV) on stock prices of companies in the consumer goods sector. The sampling method used purposive sampling. The sample used was 3 companies during the 2017-2021 period. The total data processed were 15 observations. The data used is secondary data from the company's financial statements published on the Indonesia Stock Exchange (IDX) in the form of panel data. The analysis technique used is multiple linear regression analysis. The results showed that partially and simultaneously Return On Equity (ROE) and Price to Book Value (PBV) had a significant effect on stock prices. Keywords: Stock Price; Return On Equity; Price to Book Value